Implementation of Problem Based Learning Through Outbound to Develop Emotional Intelligence in Elementary Schools - Ita Purnami; sudarti Sudarti; Bevo Wahono (Jurnal Penelitian Pendidikan IPA, 2025)
The current Generation Z often exhibits advanced technological skills but struggles with social-emotional aspects like individualism, low motivation, and lack of empathy. This study investigated how problem-based learning (PBL) via outbound activities could foster emotional intelligence in elementary students. A pretest-posttest control group experimental design was employed, involving 30 fourth-grade students from SD Negeri Tempurejo 01, Lumajang Regency. Fifteen students in Class A served as the experimental group, receiving PBL through outbound, while Class B, also with fifteen students, was the control group, taught by conventional lecture and discussion. Emotional intelligence was measured using pre- and post-tests across indicators: Self-Awareness, Self-Regulation, Motivation, Empathy, and Social Skills. One-Way ANOVA analyzed the data. Results showed a significant increase (p < 0.05) in emotional intelligence and its indicators in both groups. Crucially, the experimental group's average post-test score was significantly higher (p < 0.05) than the control groups. Motivation saw the highest increase, while Self-Regulation showed the lowest. This suggests that PBL through outbound significantly enhances elementary students' emotional intelligence development. Further strategy refinement is recommended to optimize growth across all indicators, particularly Self-Regulation